Coexpression and synexpression patterns across languages: comparative concepts and possible explanations - Haspelmath, Martin (Frontiers in Psychology, 2023)
Meanings and linguistic shapes (or forms) do not always map onto each other in a unique way, and linguists have used all kinds of different terms for such situations: Ambiguity, polysemy, syncretism, lexicalization, semantic maps; portmanteau, cumulative exponence, feature bundling, underspecification, and so on. In the domain of lexical comparison, the term colexification has become generally established in recent years, and in the present paper, I extend this wordformation pattern in a regular way (cogrammification, coexpression; syllexification, syngrammification, synexpression). These novel terms allow us to chart the range of relevant phenomena in a systematic way across the grammar-lexicon continuum, and to ask whether highly general explanations of coexpression and synexpression patterns are possible. While there is no new proposal for explaining coexpression here, I will suggest that frequency of occurrence plays a crucial role in explaining synexpression patterns.1 Linguistic expressions or forms are treated as pairs of a meaning and a shape here. It is more common to say that linguistic expressions or forms are form-meaning pairs, but the term form is then used in two different meanings ('shape' and 'shape-meaning pair'). This is why I prefer shape to form in the present context.2 An example of multiple exponence in inflection is Modern Greek é-kan-a-n [PST-do-PST-3PL] 'they did', where past tense is signaled by the prefix é-and also by the suffix -a. Multiple exponence is discussed in detail by Harris (2017).3 Meanings are associated not only with morphs (i.e. roots and markers), but often also with constructions. This is reflected in the definitions in (4) and ( 13) below, but otherwise I leave constructions (as well as idioms) out of consideration here for the sake of simplicity.